Social Development of Students Participating in Physical Activity and Computer Games - Saadi Sami; Sadigh Mahmoudi; Sarhad Aghaei (The Society of Aging and Physical Activity (SAPA), 2015)
The purpose of this study was to compare the participation in physical activity and computer games on the social development of students. The population of this research was made up entirely of male students from secondary schools in the city of Marivan (mean age of 13.5 years). Among them, 300 were selected purposively (150 athletes, 150 computer games players). In order to collect the information, Weitzman's social development scale was used. For the statistical analysis of data, n independent t-test with a significance level (P < 0.05) was used. Overall, the findings of this study suggest that the physical activity group has a higher social development than computer games group.